Synthesis of α,α-Difluorobenzylic structures via new base-promoted reductive and oxidative coupling reactions - Hooker, Leidy V., author; Bandar, Jeffrey S., advisor; Kennan, Alan, committee member; Finke, Richard, committee member; Reisfeld, Brad, committee member (Colorado State University. Libraries, 2024)
α,α-Difluorobenzylic substructures have been a desired product in a variety of industries from pharmaceuticals to agrochemicals to electronic materials. This thesis highlights the traditional and fundamental challenges associated with accessing these valuable products from trifluoromethylarenes and difluoromethylarenes, respectively, with an emphasis on base-promoted strategies to facilitate these transformations. Both a general Lewis base-promoted reductive coupling strategy and a Brønsted base-promoted oxidative coupling strategy have been developed with the purpose of achieving more modular access to α,α-difluorobenzylic substructures. Chapter One describes the significance of defluorinative strategies on small molecule organofluorines and the background of defluorinative strategies on trifluoromethylarenes, specifically, including previous and current work by the Bandar Group. The monoselective defluorofunctionalization of trifluoromethylarenes has been a long-standing challenge within the chemistry community and in 2019 the Bandar Group began to expand this methodology to include Lewis-base promoted approaches to access value-added products. Chapter One is intended to be the foundation of this thesis and convey the importance of fluorinated small molecules in a variety of applications with a specific emphasis on defluorinative strategies to functionalize trifluoromethylarenes. Chapter Two describes the long-standing challenges for selective defluorofunctionalization of trifluoromethylarenes, specifically of electronically unactivated arenes. Insight gained from the Bandar Group's reported Lewis base-promoted strategy was used to pragmatically develop an approach for selective functionalization of electron-neutral trifluoromethylarenes. This chapter will provide background on the prevalence of trifluoromethylarenes, strategies that selectively functionalize unactivated systems, and my efforts to expand Lewis-base promoted functionalization to this class of arenes. Chapter Three describes the fundamental challenge of deprotonative strategies that result in unstable carbanions, particularly α,α-difluoromethylarenes and our approach to achieve their productive functionalization. Difluorobenzylic substructures are valuable in a variety fields such as pharmaceuticals, agrochemicals, and electronic materials. Our group's Halogen transfer platform provides an approach to rapidly capture unstable carbanions with base-stable halogen oxidants (2-halothiophenes) which was sequenced with substitution via in situ pronucleophiles. The scope is highly general and provides alternative selectivity to traditional nucleophilic fluorination or radical halogenation methods, while pronucleophiles can be aliphatic alcohols or aromatic alcohols and thiols to achieve value-added products.
Keywords: difluorobenzylic structures; trifluoromethylarenes; difluoromethylarenes; base chemistry